Pembentukan Konsep Diri Remaja Melalui Penanaman Nilai-Nilai Keislaman - Adi Saputra; Yuzarion (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2020)
The purpose of the current study is to determine how self-concept forms in adolescents through inculcating Islamic values. Literature study from various sources, including abstracts of scientific writing results, journal reviews published between 2010-2018 and books related to this article, was employed as the research method. The self-concept is all our perceptions about our self-aspects, such as physical aspect, social aspect, and psychological aspect, which are based on our experiences and interactions with other people. The conclusion of this study is that family support plays a very significant role in the formation self-concepts in adolescents, where families that establish good parent-child communication can nurture positive self-concepts in their children. The self-concept develops gradually and is influenced by the closest circle like the people in the family and the views of the adolescents about themselves. In the process of forming the self-concept in adolescents, it is indispensable to instill Islamic values. With the inculcation of Islamic values, positive self-concepts can be formed in the adolescents' minds. The results of this study indicate that adolescents who are implanted with Islamic values ​​tend to have positive self-concepts, compared to adolescents whose self-concepts tend to be negative due to the lack Islamic values inculcation during the self-concept formation progress.